Effects of Maillard reaction and its product AGEs on aging and age-related diseases - Huan Peng; Yuqi Gao; Chenye Zeng; Rui Hua; Yannan Guo; Yida Wang; Zhao Wang (Food Science and Human Wellness)
Maillard reaction (MR) is a non-enzymatic browning reaction commonly seen in food processing, which occurs between reducing sugars and compounds with amino groups. Despite certain advantages based on Maillard reaction products (MRPs) found in some food for health and storage application have appeared, however, the MR occurring in human physiological environment can produce advanced glycation end products (AGEs) by non-enzymatic modif ication of macromolecules such as proteins, lipids and nucleic acid, which could change the structure and functional activity of the molecules themselves. In this review, we take AGEs as our main object, on the one hand, discuss physiologic aging, that is, age-dependent covalent cross-linking and modif ication of proteins such as collagen that occur in eyes and skin containing connective tissue. On the other hand, pathological aging associated with autoimmune and inflammatory diseases, neurodegenerative diseases, diabetes and diabetic nephropathy, cardiovascular diseases and bone degenerative diseases have been mainly proposed. Based on the series of adverse effects of accelerated aging and disease pathologies caused by MRPs, the possible harm caused by some MR can be slowed down or inhibited by artif icial drug intervention,dietary pattern and lifestyle control. It also stimulates people’s curiosity to continue to explore the potential link between the MR and human aging and health, which should be paid more attention to for the development of life sciences.